Investigation and treatment of amenorrhoea resulting in normal fertility. Issue 6173 (12th May 1979) - Hull, M G; Savage, P E; Jacobs, H S
Abstract : A simple scheme of investigation and treatment to restore fertility in amenorrhoeic women is described. Fifty-nine patients with amenorrhoea not due to primary ovarian failure were treated variously as appropriate, mainly with clomiphene (25), bromocriptine (15), or human menopausal gonadotrophins (12), and six by diet to increase their weight. All ovulated, and by the end of the study 55 (93%) had conceived, 42 (71%) had delivered at least one surviving child, and five others (8%) were pregnant and awaiting delivery. Conception rates were 49% within two cycles of treatment and 66% within three cycles; using life-table method to standardise the cumulative conception rates by correcting for patients who did not continue as long as others in the study, the expected conception rate was 79% in six cycles, 94% in 12 cycles, and 98% after 16 cycles. The multiple pregnancy rate was 13% and abortion rate 22%. Delivery rate (for a viable baby) were 48% within 11 months of starting treatment and 53% within one year; expected rates were 76% in 18 months and 97% in two years. The results show that a relatively simple scheme of classifying amenorrhoeic disorders endocrinologically followed by treatment directed at inducing ovulation allows amenorrhoeic women without primary ovarian failure to achieve conception and delivery rates equal to those in normal women.